Physics goes for gold - Jamieson, V. (Physics World, 2000)
Physical fitness is no longer enough to guarantee a gold medal at the Olympics, but an understanding of the science behind the sport may give competitors that crucial edge. Since it was lit in Athens back in May, the Olympic torch has so far travelled over 27 000 km through 13 countries-carried by snowmobile, camel, canoe and even underwater. For the thousands of participants at this year's Olympic games, the journey to Sydney has been no less arduous. It has taken strength, determination and years of intensive training to qualify for the ultimate sporting event. And as the torch is carried into the Olympic Stadium on 15 September, one thought will be at the forefront of the athletes' minds: winning.